What We Think When We Think About (Interpersonal) Violence: Understanding Knowledge Production. (July 2023) - Murshid, Nadine Shaanta
Amid growing consensus that violence against women is structurally produced, neoliberalism produces an individualist understanding of violence that blames women while simultaneously framing it as personal failings of men, obscuring the link between the structural and the personal. Using examples from federal grant funding opportunities in the United States, activism in Bangladesh, and data from qualitative research, I analyze how such individual readings of violence get produced–reproduced. I call for radical responsibility to produce equitable and just research that serves the communities that we study, not just the interests of grant funders and the neoliberal university.